PENGARUH WORK FAMILY CONFLICT DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PUSKESMAS PERAK TIMUR KOTA SURABAYA DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Prameswari, Anggraini Dian; Kistyanto, Anang; Witjaksono, Andre Dwijanto (JURNAL ILMIAH EDUNOMIKA, 2025)
Performance is the achievement of organizational goals that can be formed quantitative or qualitative output, creativity, flexibility, reliability or other things that the organization can want. Good performance is an action to achieve the goals of the organization so that efforts are needed to improve performance. The purpose of this study was to analyze the effect of work family conflict and job stress on performance with motivation as a moderating variable. This research was conducted at the Perak Timur Health Center, with saturated sampling obtained a sample of 47 respondents. Statistical data analysis with the Structural Equation Modeling (SEM) approach and Partial Least Squares (PLS) technique through SmartPLS software. The results of this study explain, among others, that work family conflict has no effect on employee performance. Furthermore, job stress has no effect on employee performance. Motivation as a moderating variable is proven to have a positive effect in influencing the relationship between work family conflict and employee performance. In addition, motivation as a moderating variable is also proven to have a positive effect in influencing the relationship between work stress and employee performance..